If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -3 = -2x + -9 Reorder the terms: -3 + y = -2x + -9 Reorder the terms: -3 + y = -9 + -2x Solving -3 + y = -9 + -2x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + y = -9 + 3 + -2x Combine like terms: -3 + 3 = 0 0 + y = -9 + 3 + -2x y = -9 + 3 + -2x Combine like terms: -9 + 3 = -6 y = -6 + -2x Simplifying y = -6 + -2x
| 12t=10 | | 22-0.8q=6+1.2q | | 6000+5045x=5795x | | 10y+8y=153 | | y-6=-2x-(-3) | | 5y-3=2y-18 | | 27t^2-6t=0 | | 12d=10 | | 5(x+2)+8x=36 | | 33= | | 2200-q^2=400+q^2 | | 3/2-1/2=x | | 3/2-1/2= | | h=10.5+6.5sin(1700) | | x+2x+3x=1320 | | 15+t=193.75 | | 12x=11.5 | | 5x=11+3y | | 60+50.45=57.95x | | 3n+18=4n+29 | | y-90=3x-100 | | 4x+34=x+97 | | -43-(-19)-(-21)+25= | | W=-3+2w | | 48+d=3.2 | | h=12.5+9sin(1500) | | 2(u-5)+5u=11 | | 14.95+0.13x=50. | | 14.95+0.13x=59. | | -94+4x=114-9x | | 48d=3.2 | | 1m-2.7=-1.5+1 |